2009
DOI: 10.1186/1471-2334-9-164
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus and Acinetobacter baumanniion computer interface surfaces of hospital wards and association with clinical isolates

Abstract: BackgroundComputer keyboards and mice are potential reservoirs of nosocomial pathogens, but routine disinfection for non-water-proof computer devices is a problem. With better hand hygiene compliance of health-care workers (HCWs), the impact of these potential sources of contamination on clinical infection needs to be clarified.MethodsThis study was conducted in a 1600-bed medical center of southern Taiwan with 47 wards and 282 computers. With education and monitoring program of hand hygiene for HCWs, the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 28 publications
(34 reference statements)
0
18
0
1
Order By: Relevance
“…Inorganic materials such as computer keyboards in the nursing station might play a role as potential reservoirs of these resistant pathogens. 20 Plasmid transfer of carbapenemase gene had also been reported. 21 The most worrisome finding was the emergence of nonsusceptibility in AGS 13TU.…”
Section: Discussionmentioning
confidence: 96%
“…Inorganic materials such as computer keyboards in the nursing station might play a role as potential reservoirs of these resistant pathogens. 20 Plasmid transfer of carbapenemase gene had also been reported. 21 The most worrisome finding was the emergence of nonsusceptibility in AGS 13TU.…”
Section: Discussionmentioning
confidence: 96%
“…An increasing drug resistance of A. baumannii to carbapenems has been demonstrated by the SENTRY Antimicrobial Surveillance Program, whose objective was to report antimicrobial susceptibility and pathogen occurrence data for >40,000 episodes of BSI in 72 medical centers representing 22 nations since January 1997 (7). The emergence of multidrug and pandrug-resistant A. baumannii has caused major threats to the infection control and treatment plans in clinical practices (8). According to our knowledge, drug resistance of A. baumannii is closely related with the application of antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%
“…In our institution, an evaluation (by TCM) was made of protective lead garments at various sites, with only 5 of 182 samples positive for any bacteria, all normal skin flora; another assessment of computer keyboards/mice recovered S. aureus , Acinetobacter spp., or Pseudomonas spp. on 17% of tested surfaces [2,4]. One study demonstrated a majority of bedside charts in the ICU were contaminated with MDR bacteria [36].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reservoirs for epidemiologically significant organisms have been demonstrated in healthcare settings. These include high-use environmental surfaces, such as door handles and handrails; patient care items such as bedside tables, bedrails, and intravenous fluid (IV) pumps; healthcare provider protective clothing such as lead aprons; and plumbing structures including drains and faucet heads, and computer equipment, among many others [2-7]. Contamination of personal protective equipment (PPE) during patient care is a mechanism for transient colonization in healthcare workers (HCW) after doffing PPE [8,9].…”
Section: Introductionmentioning
confidence: 99%